Water condensation in low pressure steam turbine : a nucleation theory - Part 1 - Mohsin, R. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
In the operation of steam turbine, it has been well understood that the presence of twophase flow due to condensation usually experienced by the low pressure stage. The increase of wetness percentage in the steam turbine could cause direct reduction in the overall efficiency of steam turbine. The significance of the steam turbine in the present day society is obvious when it is considered that over 80 % of the world's power is generated using steam driven turbines in either fossil fuelled or nuclear power stations. Despite this central position, little attention appears to have been devoted to the study of the problems associated with the operation and design of these machines in comparison with that given to other prime movers. Considerable effort has been spent on the investigation of flow in gas turbines and many of the findings are equally applicable to the dry. This first part of the nucleation theory will provide brief introduction into the formulation of condensation study in the steam turbine operation. The final part of the study will be given in the separate paper of Part II.